School work through the screen. Teaching work in Chiapas, Mexico (Praxis Educativa, 2022)
The study analyzes the school work of teachers from urban and rural preschool and primary schools in Chiapas, in response to the health emergency caused by Covid-19. The research is of a qualitative hermeneutic type, carried out from interviews with 22 professors. The analysis enabled the construction of three thematic blocks: Through the screen. Hardship, anguish and discomfort, School work. Public and private contexts of education and schools in resistance; and, the Learn at Home Program, which presents the speeches of supporters and critics of its implementation. Updating in the report, the forms of pedagogical and ethical political action with which teachers have faced this unprecedented socio-educational condition, offers a framework to rethink the reconfiguration of the relationship between school agents and families, to fight for greater equity in the education system.
Keywords: teachers; basic education; pandemic; school work